2010
DOI: 10.1007/s10735-010-9258-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of matrix metalloproteinases 2 and 9 during rat tongue carcinogenesis induced by 4-nitroquinoline 1-oxide

Abstract: Matrix metalloproteinases (MMPs) are implicated in a wide range of physiological and pathological processes, including morphogenesis, wound healing, angiogenesis, inflammation, and cancer. The purpose of this study was to characterize the role of MMPs as depicted by the expression of MMP-2 and MMP-9 during 4-nitroquinoline 1-oxide-induced rat tongue carcinogenesis. Male Wistar rats were distributed into three groups of 10 animals each and treated with 4-nitroquinoline 1-oxide solution at 50 ppm through their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Increased expression levels of MMP-9 have been observed in oral precancerous lesions as well as in oral cancer (23). The increased expression may be associated with the transformation of oral precancerous lesions to oral cancer (24,25) and in oral carcinogenesis (11). A previous in vitro study revealed that TNF-α stimulated the production of MMP-9 in a precancerous keratinocyte cell line (26).…”
Section: Discussionmentioning
confidence: 98%
“…Increased expression levels of MMP-9 have been observed in oral precancerous lesions as well as in oral cancer (23). The increased expression may be associated with the transformation of oral precancerous lesions to oral cancer (24,25) and in oral carcinogenesis (11). A previous in vitro study revealed that TNF-α stimulated the production of MMP-9 in a precancerous keratinocyte cell line (26).…”
Section: Discussionmentioning
confidence: 98%
“…A well-known way to establish an animal experimental model to study oral carcinogenesis is by the administration of the water-soluble compound 4-nitroquinoline 1-oxide (4-NQO) (Ribeiro et al 2007;Fracalossi et al 2010;Carvalho et al 2012). The medium-term assay is based on the multi-step process of carcinogenesis characterized by initiation, promotion and tumor progression.…”
Section: W Limmentioning
confidence: 99%
“…They were maintained under controlled conditions of temperature (24 ± 2°C), light-dark periods of 12 h, and with free access to water and commercial diet (Damul Science). The animals were treated for 6 months with 50 ppm 4-NQO (Sigma-Aldrich, St. Louis, USA) solution supplied in the drinking water (Fracalossi et al 2010;Miranda et al 2011). All rats were allowed access to the drinking water, which was replaced twice a week with freshly prepared solution.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…They were maintained under controlled conditions of temperature (24 ± 2°C), light-dark periods of 12 h, and with free access to water and commercial diet (Nuvital PR, Brazil). The animals were distributed into 3 groups of 10 rats each and were treated with 50 ppm 4NQO (Sigma Aldrich, St. Louis, USA) solution by drinking water for 4, 12 or 20 weeks as previously established (Miranda et al 2011;Fracalossi et al 2010). Ten animals were used as negative control and were sacrificed at the beginning the experiment (zero week).…”
Section: Animals and Experimental Designmentioning
confidence: 99%